2016
DOI: 10.1126/science.aad7969
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary neuroendocrine cells function as airway sensors to control lung immune response

Abstract: The lung is constantly exposed to environmental atmospheric cues. How it senses and responds to these cues is poorly defined. Here, we show that Roundabout receptor (Robo) genes are expressed in pulmonary neuroendocrine cells (PNECs), a rare, innervated epithelial population. Robo inactivation in mouse lung results in an inability of PNECs to cluster into sensory organoids and triggers increased neuropeptide production upon exposure to air. Excess neuropeptides lead to an increase in immune infiltrates, which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
140
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 193 publications
(153 citation statements)
references
References 28 publications
7
140
0
2
Order By: Relevance
“…Three mice from each group were analyzed, with three images taken from sections of the apex, middle, and base of the lungs of each mouse. The MLI was calculated as previously described using a 12 × 8, 50-μm grid (56). The average MLI was calculated for each mouse and then averaged within each group.…”
Section: Discussionmentioning
confidence: 99%
“…Three mice from each group were analyzed, with three images taken from sections of the apex, middle, and base of the lungs of each mouse. The MLI was calculated as previously described using a 12 × 8, 50-μm grid (56). The average MLI was calculated for each mouse and then averaged within each group.…”
Section: Discussionmentioning
confidence: 99%
“…PNECs of the bronchiolar epithelium are also thought to serve as niche cells for naphthalene-resistant variant club cells (Guha et al, 2012;Hong et al, 2001). Several studies have suggested that PNECs perform many other functions including oxygen sensing, mechanotransduction, immune cell recruitment, and chemosensing (Branchfield et al, 2016;Lembrechts et al, 2012;Pan et al, 2002). Some of these functions are presumably mediated in part through their connections with nerve fibers.…”
Section: Neuroendocrine Cellsmentioning
confidence: 99%
“…In addition to the roles described above, these major epithelial cell types are likely to possess other functions at steady state and after injury. Indeed, less frequent cell types, such as M cells and brush cells are already known to exist, and even their physiological functions are still being interrogated (Branchfield et al, 2016;Krasteva et al, 2012;Reid et al, 2005;Song et al, 2012;Teitelbaum et al, 1999). In some of the aforementioned functional cell types, such as secretory cells or type 2 cells, subsets of cells are thought to possess differing progenitor cell activities even under steady state conditions Guha et al, 2014;Reynolds et al, 2002) and much more is likely to be learned about this in the coming decade.…”
Section: Introductionmentioning
confidence: 99%
“…What signals underlie directionality and promote the integration of additional NE cells into a NEB? One possible mechanism is through the roundabout receptor (Robo), which is expressed in NEB cells: abrogation of its activity results in non-clustered, dispersed NE cells in the lung epithelium (Branchfield et al, 2016). However, further studies are clearly needed to answer these questions and gain a better understanding of this mode of epithelial cell motility.…”
Section: Lung Epithelial Neuroendocrine Mini-organs: Slithering Untilmentioning
confidence: 99%
“…4A) (Cutz et al, 2013). In pathological conditions, their unclustering is associated with increased neuropeptide release and increased immune response (Branchfield et al, 2016). Whereas single cells and small clusters are randomly scattered throughout the bronchial epithelium, large groups, referred to as NEBs, are located in a stereotyped pattern at the branchpoints of the mammalian secondary airway (which excludes the trachea and primary bronchi).…”
Section: Lung Epithelial Neuroendocrine Mini-organs: Slithering Untilmentioning
confidence: 99%